American Labor’s Global Ambassadors The International History of the AFL-CIO during the Cold War - Waters, Robert Anthony; Goethem, Geert van.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
After World War II, the AFL-CIO pursued an ambitious agenda of containing global communism and helping to throw off the shackles of colonialism. This sweeping collection brings together contributions from leading historians to explore its successes, challenges, and inevitable compromises as it pursued these initiatives during the Cold War.
Keywords: History, Modern; Civilization-History.; World history; Industrial sociology; Economic history; Social history; Modern History; Cultural History; World History, Global and Transnational History; Sociology of Work; Economic History; Social History